Effect of Red Orange Juice Consumption on Body Composition and Nutritional Status in Overweight/Obese Female: A Pilot Study. (20th March 2017) - Azzini, E.; Venneria, E.; Ciarapica, D.; Foddai, M. S.; Intorre, F.; Zaccaria, M.; Maiani, F.; Palomba, L.; Barnaba, L.; Tubili, C.; Maiani, G.; Polito, A.
Abstract : The main objective of this research was to determine whether a commercial orange juice rich in anthocyanins could have an effect on body weight and on clinical parameters related to obesity including antioxidant status, lipid profile, and metabolic and inflammatory biomarkers. 11 women with an average BMI of 34.4 ± 4.8   kg/m 2 were enrolled in a pilot study. Over a period of 12 weeks they received 500 mL daily dose into two doses (250 mL) of commercial red orange juice (COJ). The biochemical parameters were measured at baseline and at the end of the study (12 weeks). One month later upon free diet, a follow-up was performed measuring the same variables. The daily consumption of 500 mL of COJ had no significant effects on body weight, while there was a decrease in total cholesterol and LDL cholesterol. The grade of obesity implies different changes in inflammation biomarkers. In obese women, our data do not seem to support evidence that commercial red orange juice consumption acts as functional food preventing obesity and metabolic disorders such as insulin resistance and/or inflammatory status.